1964
DOI: 10.1128/jb.88.1.165-171.1964
|View full text |Cite
|
Sign up to set email alerts
|

Host Range of Certain Virulent and Temperate Bacteriophages Attacking Group D Streptococci

Abstract: Host range of certain virulent and temperate bacteriophages attacking group D streptococci. J. Bacteriol. 88:165-171. 1964.-Host range studies with five bacteriophages isolated from sewage showed that a high degree of strain specificity occurred among the species Streptococcus faecalis, S. faecalis var. zymogenes, and S. faecalis var. liquefaciens. Certain phages were able to attack various members of these subgroups but not other members. A high degree of strain specificity was also found with respect to eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1966
1966
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…During the course of studies on the characteristics of group A streptococcal bacteriophages (6), it was noted that a chloramphenicol (CM)resistant mutant streptococcus was not lysed by virulent phage, in direct contrast to the parent streptococcus. No similar results relating resistance to chloramphenicol and lysis by phage have been found in the literature, although resistance to several purine and pyrimidine analogues has been reported to alter phage sensitivity of strains of group D streptococci (2).…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…During the course of studies on the characteristics of group A streptococcal bacteriophages (6), it was noted that a chloramphenicol (CM)resistant mutant streptococcus was not lysed by virulent phage, in direct contrast to the parent streptococcus. No similar results relating resistance to chloramphenicol and lysis by phage have been found in the literature, although resistance to several purine and pyrimidine analogues has been reported to alter phage sensitivity of strains of group D streptococci (2).…”
mentioning
confidence: 57%
“…Although no report has been made of the acquisition of phage resistance by a bacterial strain after mutation to CM resistance, resistance to the pyrimidine analogue, fluorouracil, has been reported to affect phage sensitivity in a group D streptococcus, whereas resistance to 8azaguanine resulted in sensitivity to phage in another strain (2). Group A streptococci resistant to other antibiotics, such as streptomycin, erythromycin, neomycin, and vancomycin, have been found to retain their sensitivity to phage, at the resistance levels tested.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the streptococcal bacteriophage studies appearing through 1960 have been reviewed by Groman (1961) and will not be repeated here. Recent attempts to clarify the interrelationships of the ente rococci by bacteriophage typing have m e t with some encouraging results (Brock, 1964). This method of delineating subgroups within the enterococci has promise f o r the future.…”
Section: Chemical Basis Of Serological Specificitymentioning
confidence: 99%
“…Transduction of enterococci has not been accomplished (Brock, 1964), s o experiments such as those conducted by Allen, Sandine and Elliker (1963) on s. lactis ( s e e also San-' dine e_t g . , 1962) cannot yet be c a r r i e d out with the fecal streptococci.…”
Section: Chemical Basis Of Serological Specificitymentioning
confidence: 99%
“…of strains of Streptococcus faeculiir. Brock (1964) showed that there was a high degree of strain specificity in the reactions of organisms of the species Str. faecalis, Str.…”
mentioning
confidence: 99%